NORMALISASI HUBUNGAN DIPLOMATIK TURKI-ISRAEL TAHUN 2016 - Muhammad Zikril Aziz; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study is an international research study in the study of diplomacy and security strategy. That describes the normalization of Turkey-Israel diplomatic relations. This study wants to know why Turkey normalizes diplomatic relations with Israel. Previously Turkey and Israeli relations went well, but there were problems causing Turkey and Israeli relations to separate. This is the reason why authors are interested in this research. In 2010, there was an incident involving Mavi Marmara ship which caused the loss of life of nine Turkey citizens. Then after the incident Turkey took action to sever diplomatic relations with Israel.This is a qualitative study that uses descriptive expressive methods. This paper uses a realist perspective and national interest theory proposed by Jack C. Plano and Roy Olton and the concept of normalization by Robert P. Barston. The author uses state-level analysis, because the conflict involves two countries. It is a method to explain problems in library research and separate research methods, such as books, journals, magazines, electronic media, and other sources.The results of this study explain that there are some national interests for Turkey such as security, military and defense, and energy on Israel. So Turkey took action to normalize diplomatic ties with Israel based on several conditions put forward by Turkey. At the final negotiations the two countries agreed to improve relations with the agreement on compensation to be paid by Israel to Turkey.Keywords: Mavi Marmara, Normalization, Diplomatic Relations, Agreements